Electrostatic bonding of silicon-to-ITO coated #7059 glass using Li-doped oxide interlayer - Jeong, JW; Ju, BK; Lee, DJ; Lee, YH; Oh, MH; Choi, DJ (KOREAN PHYSICAL SOC, 1998)
Silicon to In2O3:Sn (ITO) coated glass bonding has been developed for the packaging of Field Emitter Arrays (FEAs) fabricated on silicon wafer. This paper will focus on the processing and results for silicon-to-ITO coated glass bonding using anodic bonding process. Lithium oxide doped layer was deposited on ITO coated glass by electron beam evaporation. The breakdown voltage of lithium doped oxide interlayer was investigated with the comparison of Sputtered #7740. Silicon-to-ITO coated glass bonding occurs in the range of temperatures from 260 degrees C to 320 degrees C with applied voltages ranging from 140 V-DC to 220 V-DC. The bonding strength obtained from tensile test was about 10 MPa under condition of 180 V-DC in 320 degrees C. In order to study the role of the lithium ions in the bonding mechanism, secondary ion mass spectroscopy (SIMS) analysis was carried out. The possibility of the packaging method of FED is proposed.